Gonorrhea: Antimicrobial Resistance and New Drugs - Catarina Soares Queirós; João Borges da Costa (Sociedade Portuguesa de Dermatologia e Venereologia, 2019)
The global burden of sexually transmitted infections remains high, with significant associated morbidity and mortality. Gonorrhea is the second most notified sexually transmitted infection in Europe, and its incidence has been increasing in the last years. Although traditionally considered a treatable infection, antimicrobial resistance of Neisseria gonorrhoeaeincludes at present also macrolides, tetracyclines, sulfonamides and trimethoprim combinations, quinolones, and even cephalosporins. These high levels of gonococcal resistance to antimicrobials resulting in untreatable infections in the future may become one of the greatest challenges to the prevention and control of sexually transmitted infections, which may be a significant major public health issue. Therefore, the development of novel antimicrobials and/or new dual antimicrobial therapy regimens is urgently needed. In this paper, evolution of antimicrobial resistance of Neisseria gonorrhoeae is reviewed, along with new drugs currently under development for the treatment of this infection.